POLICY ON SETTING TIME LIMITS FOR THE RESOLUTION OF JUVENILE CRIMINAL CASES AT THE FIRST-INSTANCE TRIAL STAGE BASED ON THE PRINCIPLE OF JUSTICE: Formulasi Kebijakan Penetapan Batas Waktu Penyelesaian Perkara Pidana Anak pada Tahap Persidangan Tingkat Pertama Berdasarkan Asas Keadilan - Nurul Palah; Prija Djatmika; Bambang Sugiri (PT. Radja Intercontinental Publishing, 2026)
This study examines the policy formulation regarding time limits for the resolution of juvenile criminal cases at the first-instance trial stage based on the principle of justice. The research focuses on the urgency of establishing clear procedural time limits in juvenile criminal proceedings, particularly in cases where diversion fails to achieve an agreement and the matter proceeds to court. The study employs a normative juridical method using statutory, conceptual, and analytical approaches to examine the Juvenile Criminal Justice System Law, the New Criminal Procedure Code, and Supreme Court regulations related to judicial administration. The findings reveal that the absence of explicit regulations concerning time limits for juvenile case examinations creates legal uncertainty, prolongs judicial proceedings, and potentially affects the psychological condition and legal protection of children in conflict with the law. Furthermore, inconsistencies between procedural regulations and restorative justice mechanisms hinder the realization of effective and child-centered justice. Therefore, this study proposes an ideal criminal law policy (ius constituendum) through the establishment of specific time limits, judicial supervision mechanisms, and administrative sanctions to ensure expedited case resolution while maintaining restorative justice principles and prioritizing the best interests of the child.